2010
DOI: 10.1177/0956797610374742
|View full text |Cite
|
Sign up to set email alerts
|

Cosmetic Use of Botulinum Toxin-A Affects Processing of Emotional Language

Abstract: How does language reliably evoke emotion, as when reading a favorite novel or listening to a skilled orator? Recent evidence suggests that comprehension involves a mental simulation of sentence content that calls on the same neural systems used in literal action, perception, and emotion. Here we demonstrate a causal role of involuntary facial expression in the processing of emotional language. Subcutaneous injections of botulinum toxin-A (BTX) were used to temporarily paralyze the facial muscle used in frownin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
164
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(180 citation statements)
references
References 30 publications
12
164
0
4
Order By: Relevance
“…The relationship between the expression and experience of emotions is a long-standing topic of heated disagreement in the field of psychology (10,29,30). Central to this debate, studies on facial feedback have shown that forced induction of a smile or a frown or temporary paralysis of facial muscles by botulinum injection leads to congruent changes in the participants' emotional reactions (11,(31)(32)(33). Although these experiments support the general notion that emotional expression influences experience, they all suffer from problems of experimental peculiarity and demand.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the expression and experience of emotions is a long-standing topic of heated disagreement in the field of psychology (10,29,30). Central to this debate, studies on facial feedback have shown that forced induction of a smile or a frown or temporary paralysis of facial muscles by botulinum injection leads to congruent changes in the participants' emotional reactions (11,(31)(32)(33). Although these experiments support the general notion that emotional expression influences experience, they all suffer from problems of experimental peculiarity and demand.…”
Section: Discussionmentioning
confidence: 99%
“…popularity [7][8][9][10][11]. In one study, BTA in the forehead was compared to other cosmetic treatments (i. e., BTA in other regions besides the forehead, Restylane, glycolic peels, and laser treatments) [9].…”
mentioning
confidence: 99%
“…Studies have also shown that basic movement kinetics, processed atypically in ASC, offer clues to the emotional and mental states of others (Hubert et al, 2007;Patel, Fleming, & Kilner, 2012). In the language domain, processing of emotion-related language is affected by manipulation of facial musculators (Glenberg, Havas, Becker, & Rinck, 2005;Havas, Glenberg, Gutowski, Lucarelli, & Davidson, 2010) or damage to white matter just adjacent to motor cortex (Dreyer et al, 2015). This evidence implies a potentially causal link between the motor hypoactivity we observed in ASC during processing of emotion words, and the emotion word processing deficits noted above in behavioural studies.…”
mentioning
confidence: 99%